Cross-Stress Adaptation in a Piezophilic and Hyperthermophilic Archaeon From Deep Sea Hydrothermal Vent - Zhao, Weishu; Ma, Xiaopan; Liu, Xiaoxia; Jian, Huahua; Zhang, Yu; Xiao, Xiang (Frontiers in Microbiology, 2020)
Hyperthermophiles, living above 70°C and usually coupling with multi-extreme environmental stresses, have drawn great attention for their application potential in biotechnology and primitive extant forms of life. Studies on their survival and adaptation mechanisms extend our understanding on how life thrives under extreme conditions. During these studies, the “cross-stress” behavior in various organisms has been observed between the extreme high temperature and other environmental stresses. Despite the broad observation, the global view of the cross-stress behavior remains unclear in hyperthermophiles, leaving a knowledge gap in our understanding of extreme adaptation. In this study, we performed a global quantitative proteomic analysis under extreme temperatures, pH, hydrostatic pressure (HP) and salinity on an archaeal strain, Thermococcus eurythermalis A501, which has outstandingly wide ranges of growth capability on temperatures (50-100oC), pH (4-9) and hydrostatic pressures (0.1-70 MPa), but a narrow range on NaCl (1.0-5.0 %, w/v). The proteomic analysis (79.8% genome coverage) demonstrated that approximately 61.5 % of the significant differentially expressed proteins (DEPs) responded to multiple stresses. The responses to most of the tested stresses were closely correlated, except the responses to high salinity and low temperature. The top three of the enriched universal responding processes include the biosynthesis and protection of macromolecules, biosynthesis and metabolism of amino acids, ion transport and binding activity. In addition, this study also revealed the specific dual-stress responding processes, such as the membrane lipids for both cold and HP stresses, the signal transduction for both hyper-osmotic and heat stresses, as well as the sodium-dependent energetic processes might be the limiting factor of the growth range in salinity. The present study is the first to examine the global cross-stress response in a piezophilic hyperthermophile at proteomic level. Our findings provide direct evidence of the cross-stress adaptation strategy (33.5% of coding-genes) to multiple stresses and highlight the specific and unique responding processes (0.22%-0.63% of coding-genes for each) to extreme temperature, pH, salinity and pressure, which are highly relevant to the fields of evolutionary biology as well as next generation industrial biotechnology (NGIB).